PERTUMBUHAN HUTAN TANAMAN JATI (Tectona grandis Linn.f.) DI KALIMANTAN TIMUR - Veronika Murtinah , Marjenah, Afif Ruchaemi dan Daddy Ruhiyat (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
The Growth of Teak Plantation Forest in East Kalimantan. Teak is one of the most important tropical timber in the international timber market because of the various advantages it has and the type of wood that is very valuable for forestry plants. Teak has been known and cultivated for a long time, particularly in Java. In East Kalimantan, Teak has been developed by public and private companies , with a growth of diverse.The growth of teak stands in East Kalimantan in general showed a decline in growth with increasing stand age; diameter and height growth of stands highest in the early phase of growth in the range of 1-5 years of age, then decline gradually and growth has declined after the 12 year old stands; up to 12 year old stands generally teak growth in East Kalimantan showed growth (increment) in diameter and a height higher than the other locations teak plantation in Java.